PENERAPAN PEMBELAJARAN MATEMATIKA REALISTIK UNTUKMENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA PADA MATERI BANGUN RUANG SISI LENGKUNG DI KELAS IX MTs AL-WASLIYAH TEMBUNG - Chairul Riva’i; Edy Surya (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2013)
This study aims to determine whether the increased student learning outcomes with realistic mathematics education on the material side of the curves geometry in class IX MTs Al-Washliyah Tembung academic year 2014/ 2015. This type of reasearch is a classroom action research. Subjects in this study were 32 students of class IX-D MTs Al-Washliyah Tembung and the object of theis study is an effort to improve student learning outcomes with realistic mathematics education. The instruments used in the study was the observation ans tests. The result is an average 2.9 observations of category realistic mathematics learning process on the material side of the curved ge between cycle I and II, and through the provision of test results obtained by 30 students studying II (93.75 %) of 32 students have achieved matery leaarning (value 65), while 2 students (6.25 %) have not been completed. Based on the descreptions above concluded that increased student learning outcomes with realistic mathematics education on the material side of the curved geometry in class IX MTs Al-Washliyah Tembung academic year 2014/ 2015.